(untitled) (Research, Society and Development, 2020)
Peritoneal Dialysis is a treatment modality for patients with Chronic Kidney Disease and presents benefits such as the return of patients to a practically normal life due to the autonomy of self-care and easy of treatment at home. The aim of the study was to understand the perception of patients undergoing peritoneal dialysis treatment regarding the risks of infections during home aseptic practices. It´s descriptive study of a qualitative approach developed conducted from March to June 2019 in a Private Clinic of Nephrology of Teresina-PI. The study included Adult patients on Peritoneal Dialysis treatment older than 18 years were included in the study and excluded those who were debilitated, with cognitive or psychological restrictions. For data collection it was used a semi-structured interview script with data on the sociodemographic characteristics of the interviewed group, and the second with open questions about the risks of infection and care with the PD catheter. Results were interpreted and discussed according to Content Analysis. Most patients were found to have infection at the catheter outlet and in some cases to peritonitis, which were possibly acquired by procedural errors during self-care with the Peritoneal Dialysis catheter. Even after receiving instructional training by the health team about the treatment, material used, home care, aseptic methods, among others, the patients had difficulties in the handling of the DP catheter. It is necessary that the multidisciplinary health team rethink the logic of knowledge construction of patients with peritoneal dialysis, seeking to identify the approach that guides treatment when performed at home.